Penguatan Kompetensi Guru Melalui Pelatihan Dan Pendampingan Pembuatan Media Pembelajaran Kartu BiZi Bagi Guru Bahasa Arab Di Jombang - Afif Kholisun Nashoih; Khotim Fadhli; Akhmad Taqiyuddin; Abdul Khorib; Ima Ni’matus Sholikhah; Chumairoh Putriningtyas (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2022)
The preservation of conservative traditional methods in learning Arabic at the elementary level is a classic problem that needs to be given a sustainable solution. The innovation and creativity of teachers in conveying information has an impact on the success of learning and or the achievement of learning objectives. Utilization of learning media is one solution to these problems. The results of this study became the issues raised in mentoring and training activities to make BiZi card learning media for teachers at MI Muhammadiyah Rejosopinggir Jombang, with the hope that Arabic language learning would become attractive and effective learning. The implementation of this community service uses the Community Based Research (CBR) method which is carried out through training and mentoring for teachers at MI Muhammadiyah Rejosopinggir for 5 days. The activity stages started with the presentation of material about the importance of learning media, the practice of designing computing-based cards, and making BiZi cards of various sizes, then closed with an evaluation. The results of this service indicate that teachers gain new motivation and knowledge in order to improve their competence in utilizing and using learning media. After the training was carried out, the Arabic learning process could take place in a pleasant atmosphere, and students seemed actively involved in learning. In the practice carried out during mentoring, the teacher began to apply arabic language skills which included maharah istima', kalam, qira'ah, and kitabah during the learning process. And in the practice carried out during mentoring, it is known that teachers are starting to facilitate more and more students to be actively involved in the learning process, because there is reciprocity with students.